West African Languages : Medium and Message - Easton, Peter (World Bank, Washington, DC, 2012)
Indigenous knowledge in Africa, and the world over, is expressed in language, and usually in an "indigenous" language - in short, the mother tongue of inhabitants of the locality, or a lingua franca in regular usage by them. Are these languages simply a neutral medium? Are they just instrumental "vehicles" for the expression of local knowledge and daily life? Or do the languages themselves play some role, by their very structure and usage, in what is thought and known? The examples in this Note are principally drawn from Hausa, the second most widespread tongue in Africa and a member of the "Chadic" group of languages. It is principally spoken in northern Nigeria and central Niger, but is used as well as in several other countries of the region. The patterns are nonetheless roughly representative of a host of western and central African language traditions.